2012
DOI: 10.5812/hepatmon.5805
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Occult Hepatitis B Virus Infection in Hemodialysis Patients From Egypt With or Without Hepatitis C Virus Infection

Abstract: Background: While prevalence of Hepatitis B virus (HBV) in patients with end-stage renal failure (ESRF) who are undergoing dialysis has decreased significantly during the past few decades, it still remains a distinct clinical problem. The immunosuppressive nature of renal disease often leads to chronicity of the HBV infection and an opportunity for nosocomial spread of the infection among dialysis patients. Egypt is among the countries with intermediate endemicity of HBsAg (range, 2%-7%). Large-scale geographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 28 publications
4
23
0
Order By: Relevance
“…The present study results show significant differences in regard to sex had higher in male than female between hemodialysis patients with HBV or HCV infection. In accord [12] [14] studies results which did not show significant differences in regard to age between hemodialysis patients with HBV or HCV infection compared with hemodialysis patients without HBV or HCV infection whereas, this does not comply with [21] study that reported a statistically significant relationship between HBV infection and age of the patients in a way that patients aged less than 40 years were found to be more susceptible to HBV than older patients. This observation is in agreement with a previous report from Libya showing that the highest prevalence of HCV antibodies was observed in HD patients aged 36 -55 years [17].…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…The present study results show significant differences in regard to sex had higher in male than female between hemodialysis patients with HBV or HCV infection. In accord [12] [14] studies results which did not show significant differences in regard to age between hemodialysis patients with HBV or HCV infection compared with hemodialysis patients without HBV or HCV infection whereas, this does not comply with [21] study that reported a statistically significant relationship between HBV infection and age of the patients in a way that patients aged less than 40 years were found to be more susceptible to HBV than older patients. This observation is in agreement with a previous report from Libya showing that the highest prevalence of HCV antibodies was observed in HD patients aged 36 -55 years [17].…”
Section: Discussionsupporting
confidence: 67%
“…Overall, the prevalence and incidence of HBV and HCV infections in HD patients reflects the prevalence of these infections in the general population, the quality of healthcare services in a community and the standards of infection control practices in HD units are related. The results of [20] study, showed that male hemodialysis patients had higher HBV prevalence, whereas [14] study showed that male hemodialysis patients had higher HCV prevalence. These results are in disagreement with the results of study [12].…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…In one recent study of haemodialysis patients in Egypt who were negative for HBsAg, hepatitis B DNA was detected in 4.1% and HBcAb in 20%. 37 It is therefore possible that we failed to detect cases of occult hepatitis B infection.…”
Section: Discussionmentioning
confidence: 98%
“…The prevalence of OBI in HD patients varies markedly from one locality to another worldwide, with a range of 0% to 36 % (13) . In Egypt, the prevalence was reported at 4% in Minia and Assuit (Upper Egypt) and reached 26.8% among patients in Alexandria (North Egypt) (23) (24) . Even with these recent data addressing the prevalence of OBI in patients on HD in Egypt, more comprehensive data may be needed to evaluate OBI among chronic HCV carriers and to determine whether the prevalence differs following HD, as both HCV carriers and chronic HD patients may serve as a potential source for the spread of OBI in the community.…”
Section: Methodsmentioning
confidence: 99%